Direct three-dimensional printing of polymeric scaffolds with nanofibrous topography - Yang, Jing; Shakesheff, Kevin M.; Prasopthum, Aruna (IOP Publishing, 2018)
Three-dimensional (3D) printing is a powerful manufacturing tool for making 3D structures with well-defined architectures for a wide range of applications. The field of tissue engineering has also adopted this technology to fabricate scaffolds for tissue regeneration. The ability to control architecture of scaffolds, e.g. matching anatomical shapes and having defined pore size, has since been improved significantly. However, the material surface of these scaffolds is smooth and does not resemble that found in natural extracellular matrix (ECM), in particular, the nanofibrous morphology of collagen. This natural nanoscale morphology plays a critical role in cell behaviour. Here, we have developed a new approach to directly fabricate polymeric scaffolds with an ECM-like nanofibrous topography and defined architectures using extrusion-based 3D printing. 3D printed tall scaffolds with interconnected pores were created with disparate features spanning from nanometres to centimetres. Our approach removes the need for a sacrificial mould and subsequent mould removal compared to previous methods. Moreover, the nanofibrous topography of the 3D printed scaffolds significantly enhanced protein absorption, cell adhesion and differentiation of human mesenchymal stem cells (MSCs) when compared to those with smooth material surfaces. These 3D printed scaffolds with both defined architectures and nanoscale ECM-mimicking morphologies have potential applications in cartilage and bone regeneration.